2018
DOI: 10.1002/pat.4314
|View full text |Cite
|
Sign up to set email alerts
|

A new cross‐linked system of silicone rubber based on silicone‐polyurea block copolymer

Abstract: A new cross‐linked system of silicone rubber (SR) was obtained from silicone‐polyurea block copolymers that was synthesized with aminopropyl terminated polydimethylsiloxane and (4‐isocyanatocyclohexyl)‐methane. SR possessed self‐reinforced and physical cross‐linked structure. It had better mechanical properties that the hardness, the tensile strength, and the elongation at break could reach 65 Shore A, 3.78 MPa, and 458% with the polyurea segment content ranging from 2.01% to 9.13% by weight. The hydrogen bond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Besides, the N−H bending vibration (1400 cm −1 ) belonging to the urea group appeared in the CAFs, but its position was slightly shifted compared with the N−H bending vibration (1540 cm −1 ) on the urea group in polyurea. 45,46 Additionally, the O− H stretching vibration corresponding to the BC matrix at 3350 cm −1 , however, with the increase of polyurea content in CAFs, gradually disappeared. 47 Based on SEM image analysis of CAFs, it could be concluded that −NCO contained in polyurea could react with −OH in the BC matrix, leading to the tight coating of polyurea nanoparticles on BC nanofibers and contributing to the hydrophobicity of CAFs (Figure 1g).…”
Section: Resultsmentioning
confidence: 99%
“…Besides, the N−H bending vibration (1400 cm −1 ) belonging to the urea group appeared in the CAFs, but its position was slightly shifted compared with the N−H bending vibration (1540 cm −1 ) on the urea group in polyurea. 45,46 Additionally, the O− H stretching vibration corresponding to the BC matrix at 3350 cm −1 , however, with the increase of polyurea content in CAFs, gradually disappeared. 47 Based on SEM image analysis of CAFs, it could be concluded that −NCO contained in polyurea could react with −OH in the BC matrix, leading to the tight coating of polyurea nanoparticles on BC nanofibers and contributing to the hydrophobicity of CAFs (Figure 1g).…”
Section: Resultsmentioning
confidence: 99%
“…1(i), which matches the silicone rubber XRD pattern documented in the literature. 51–53 The diffraction maxima at 22.3° and 12.2° are attributed to the –Si–O–Si– amorphous phase and the polyurea units, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanical properties of polyurea can be tuned by choosing different variations of diamines and diisocyanates as well as by adding assorted nano-inclusions and micro-inclusions to create polyurea-based composites [5,66,67]. Nano-inclusions and micro-inclusions dispersed in the matrix can also improve the interfacial strength of the material, resulting in some enhancement [68].…”
Section: Incorporation Of Reinforcing Materialsmentioning
confidence: 99%